TMS Shows Promise in Preventing Relapse in Patients with Resistant Depression - Nierengarten, Mary Beth (MD Conference Express, 2014)
For patients with treatment-resistant depression, long-term maintenance therapy with 1 weekly session of repetitive transcranial magnetic stimulation (rTMS) shows promise in preventing relapse in patients who respond to acute rTMS treatment. This article presents preliminary results on a 1-year, double-blind, randomized controlled trial evaluating the efficacy of rTMS as maintenance therapy for patients with treatment-resistant depression.